2017
DOI: 10.30935/cedtech/6201
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Foreign Language Learners’ Roles and Outputs: Introducing an Innovation and Role-Playing in Second Life

Abstract: This study aims to design of the two activities "introducing an innovation" and "role playing" in Second Life (SL) and to evaluate qualitatively Turkish foreign language learner's roles and outputs before, while, and after the implementation of the activities. The study used community of inquiry model consisting of cognitive presence and social presence as a theoretical frame to discuss the roles and outputs. The participants were twelve students and two English teachers from two different high schools. Teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The second line of inquiry is on the roles and impact of those Presences. In particular, research has focused on how those presences contributed to effective online language teaching and learning that led to successful performances (see, for example, Batardière, 2015;Konstantinidis & Goria, 2016;Rodriguez, 2016;Ozbek et al, 2017;Rubio et al, 2018;Schumann, 2019). For example, Ozbek et al's (2017), demonstrated that English teachers' TP in a Turkish university's English class undertaken in Second Life, an online virtual world, positively affected communicative engagement amongst English-as-a-Foreign language (EFL) students.…”
Section: Learning Presence As a Concept In Coi: A Continuing Conversationmentioning
confidence: 99%
“…The second line of inquiry is on the roles and impact of those Presences. In particular, research has focused on how those presences contributed to effective online language teaching and learning that led to successful performances (see, for example, Batardière, 2015;Konstantinidis & Goria, 2016;Rodriguez, 2016;Ozbek et al, 2017;Rubio et al, 2018;Schumann, 2019). For example, Ozbek et al's (2017), demonstrated that English teachers' TP in a Turkish university's English class undertaken in Second Life, an online virtual world, positively affected communicative engagement amongst English-as-a-Foreign language (EFL) students.…”
Section: Learning Presence As a Concept In Coi: A Continuing Conversationmentioning
confidence: 99%